CAREER DEVELOPMENT DAN WELFARE ALLOWANCES TERHADAP EMPLOYEE PERFORMANCE PADA KARYAWAN LEMBAGA AMIL ZAKAT - Irma Noor Fitriastari Fitriastari; Muzakki Muzakki (Ulumuna: Jurnal Studi Keilsman, 2023)
This study aims to explore and analyze the influence of career development and welfare benefits on employee performance at amil zakat institutions. The method used is a quantitative method that focuses on hypothesis testing. The sample used was 45 employees, using a random sampling technique. Data was collected by distributing questionnaires which were then processed using SPSS tools through multiple linear regression techniques. We consider validity and reliability to determine the reliability of the research statement items. Then, this study also considers classic assumptions such as normality, multicollinearity, and heteroscedasticity. After all that is fulfilled, then the hypothesis testing is carried out. The findings of this study prove that career development and welfare benefits have a significant positive effect on employee performance.